Multi-Year Reproducibility of Hyperinsulinemic Euglycemic Clamp-Derived Insulin Sensitivity in Free-Living Adults: Association with Incident Prediabetes in the POP-ABC Study - James, Deirdre (Metabolism, 2020)
OBJECTIVE: The hyperinsulinemic euglycemic clamp (HEC) is the “gold standard” for measuring insulin sensitivity (Si-clamp). Here, we determined the reproducibility of serial HEC data in healthy subjects. RESEARCH DESIGN AND METHODS: The Pathobiology of Prediabetes in A Biracial Cohort study assessed incident prediabetes in healthy African Americans (AA) and European Americans (EA) with parental type 2 diabetes mellitus during 5.5 years of follow-up. Assessments included anthropometry, OGTT, and HEC. Ninety subjects (44 AA, 46 EA) who underwent Year-1 HEC consented to Year-3 HEC. We calculated coefficients of variation (CVs), 95% limits of agreement, and repeatability coefficients for Year-1 and Year-3 data, and assessed the association of change in Si-clamp with incident prediabetes. RESULTS: The mean (SD) baseline age was 47.5 ± 8.13y, body mass index was 30.4 ± 9.16 kg/m(2), fasting plasma glucose was 93.7 ± 7.82 mg/dl and 2-hrPG was 126 ± 26.8 mg/dl. Si-clamp (umol/kg/min.pmol/L-1) was 0.071 ± 0.04 in Year 1 and 0.067± 0.04 in Year 3 (P =0.22). Year 1 and Year 3 values were strongly correlated (r=0.81, P<0.0001); the CV was 13.6% and repeatability coefficient was ± 0.025. Intrasubject differences in serial Si-clamp were less than the repeatability coefficients and within the 95% limits of agreement. After 5.5 years of followup, 40 subjects progressed to prediabetes and 50 were nonprogressors. The change in Si-clamp was greater in progressors than nonprogressors (−10% vs. −2.5%, P=0.02). CONCLUSIONS: The HEC is reproducible over ~2 years in free-living individuals, with a temporal decline in Si-clamp that predicts prediabetes risk.